Kinetic modeling for direct synthesis of dimethyl ether from syngas over a hybrid Cu/ZnO/Al2O3/ferrierite catalyst - Park, Jongmin; Woo, Yesol; Jung, Hyun Seung; Yang, Haelin; Lee, Won Bo; Bae, Jong Wook; Park, Myung June (Catalysis Today, 2022)
A kinetic model for the direct synthesis of dimethyl ether (DME) from syngas over a hybridized Cu/ZnO/Al2O3/ferrierite (CZA/FER) catalyst was developed. Kinetic parameters including reaction rate and equilibrium constants were estimated by fitting experimental data for the hybrid catalyst, and these were compared with the reported values for conventional catalysts. High activation energies for the hybrid CZA/FER catalyst showed that the methanol synthesis step may have more control over the rate than the methanol dehydration step. This may be attributed to the core-shell structure of the hybrid catalyst in such a way that the diffusion resistance plausibly plays an important role in the kinetics; this feature was reflected in our estimated kinetic parameters. Using the developed kinetic model, a temperature between 200 and 220 °C was determined for thermal energy efficiency, and a further analysis provided the optimal range of the total pressure and space velocity.
Keywords: Conventional catalyst; Core shell structure; Diffusion resistance; High activation energy; Hybrid catalysts; Kinetic modeling; Methanol dehydration; Methanol synthesis; Dimethyl ether; Direct synthesis; Hybrid catalyst; Kinetic model; Operating conditions; Parameter estimation